Crisis management and public policies. The trend toward regulatory practices in some countries / Gestão de crises e políticas públicas. A tendência para as práticas regulamentares em alguns países - Cruz Hernández, Pablo Armando; Méndez Bahena, Benjamín José; Culebro Moreno, Jorge Enrique (Revista de Direito da Cidade, 2023)
Abstract The article aims to investigate whether governments tend to implement regulatory policies in response to the Covid-19 pandemic and to examine the type of citizen response to different types of policies. Given that active and collaborative citizen participation is an essential element of adequate crisis management, citizen resistance, active opposition, and demonstrations in public spaces are detrimental to the successful outcome of government poli cies in the face of a crisis. We employ the crisis management and institutional analyses theoretical perspectives, as well as the qualitative methods of study case and the comparative studies. We review the different types of policies implemented in different countries. Our analysis shows that there is indeed a tendency for implementing regulatory policies. It also identifies that the places where regulative policies are created and implemented wit hout taking into account contextual aspects, it usually catalyzes citizen’s discomfort. Therefore, we argue that the type of policy used is relevant to deciding what governments’ responses should be and their effect on legitim acy during crises. Keywords: COVID-19, Crisis Management, institutional analysis, normative, regulative. Resumo O artigo pretende investigar se os governos tendem a implementar políticas reguladoras em resposta à pandemia de Covid-19 e examinar o tipo de resposta dos cidadãos aos diferentes tipos de políticas. Dado que a participação a tiva e colaborativa dos cidadãos é um elemento essencial de uma gestão adequada da crise, a resistência dos cidadãos, a oposição ativa, e as manifestações em espaços públicos são prejudiciais para o êxito das políticas governa mentais face a uma crise. Utilizamos as perspectivas teóricas de gestão de crises e análises institucionais, bem como os métodos qualitativos de estudo de casos e os estudos comparativos. Analisamos os diferentes tipos de polí ticas implementadas em diferentes países. A nossa análise mostra que existe de fato uma tendência para a implementação de políticas de regulação. Também identificamos que os locais onde as políticas reguladoras são criadas e i mplementadas sem ter em conta aspectos contextuais, geralmente catalisam o desconforto do cidadão. Portanto, defendemos que o tipo de política utilizada é relevante para decidir quais devem ser as respostas dos governos e o se u efeito na legitimidade durante as crises. Palavras-chave: COVID-19, Gestão de Crise, análise institucional, normativa, reguladora.